Verbal and Non-Verbal Signs in Movie Posters Entitled “The Boss Baby 2: Family Business” - Arie Susanti, Ni Kadek; Isnu Maharani, Sang Ayu; Weddha Savitri, Putu (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2026)
This research entitled Verbal and Non-Verbal Signs in Movie Posters Entitled “The Boss Baby 2: Family Business” aimed at identifying and conveying the meaning of verbal and non-verbal signs that are found in “The Boss Baby 2: Family Business” movie posters. 4 movie posters from “The Boss Baby 2: Family Business” movie applied as the data source in this undergraduate thesis. The data was taken through a safari application on websites. It was collected based on a documentation method and analyzed with a qualitative method and triangulation technique. Informal method also applied to present the analysis in this undergraduate thesis. The theory of Semiotics proposed by Saussure (1983) and Dyer (2009) applied to find out the verbal and non-verbal signs in movie posters. Furthermore, the theory proposed by Barthes (1977) applied to convey the meaning of verbal and non-verbal signs (that are found in “The Boss Baby 2: Family Business” movie posters). In addition, this undergraduate thesis is supported by the theory of Semantics related to color meaning by Chapman (2010). The data analysis shows that The Boss Baby 2: Family Business movie posters contain 14 Verbal signs with 14 denotative meanings as well as their color’s meaning. There were 12 non-verbal signs consisting of 12 appearances, 12 manners, 4 activities, 1 prop with non-specific setting, and 12 photographs with 12 connotative meanings as well as their color’s meaning found in the movie posters. Keywords: Verbal Signs, Non-Verbal Signs, The Boss Baby 2, Movie Poster